PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT KINARYA SELARAS PIRANTI CABANG JAKARTA SELATAN - Nur'aini, Wildi; Dja'far, Abu Bakar (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to examine the extent of the Effect of Work Stress and Work Environment on Employee Performance at PT Kinarya Selaras Piranti. This study used quantitative research methods and involved a sample population of 55 employees. The sample technique used is a saturated sample, the data collection method used is a quantitative methods. This research obtained Stress affects employee performance. Based on the results of the first hypothesis test obtained from the calculated value of the hypothesis test, the calculated value of the > ttable (9.250 >1.674) and the results of the simple regression test Y = 15.719 + 0.878 X1 were also strengthened with a sig value of < 0.05 or (0.000 < 0.05). Thus, H0 is rejected and H1 is accepted, this shows that Stress has a significant effect on Employee Performance at PT Kinarya Selaras Piranti. Based on the results of the second hypothesis test obtained from the calculated value of > ttable or (11,239> 1.674) and the results of a simple regression test Y = 11.774 + 0.680 X2. It can also be strengthened by a sig value of < 0.05 or (0.000 < 0.05). Thus H0 is rejected and H2 is accepted. This shows that the Work Environment affects the performance of employees at PT Kinarya Selaras Piranti. Based on the results of testing the third hypothesis obtained the value of Fcalculate > Ftable or (67.702 > 3.175) and the result of multiple linear Y = 10.726 + 0.287 X1 + 0.503 X2. Thus, H0 is rejected and H3 is accepted, this shows that simultaneously the variables of Stress and Work Environment influence on Employee Performance at PT Kinarya Selaras Piranti